2020
DOI: 10.1097/nur.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Related Social Interactions as Experienced by Persons Who Smoked Long-term

Abstract: Purpose/Aims: Smoking-related stigma is manifested in the everyday social interactions of persons who smoke and can result in low self-esteem, diminished self-efficacy, and resistance to smoking cessation. The purpose of this study was to describe smoking-related social interactions as experienced by persons with a history of long-term smoking.Design: Qualitative descriptive.Methods: This study is part of a larger study designed to identify factors that influence lung cancer screening participation. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Such communication efforts should aim to avoid stigmatizing smoking behaviors, an issue raised by participants in our study and found in previous research. 64,65 Our study also suggests that trust-building should entail efforts to acknowledge, understand, and reduce the present-day incidence of harmful patient experiences with practitioners.…”
Section: Jama Network Open | Oncologymentioning
confidence: 80%
“…Such communication efforts should aim to avoid stigmatizing smoking behaviors, an issue raised by participants in our study and found in previous research. 64,65 Our study also suggests that trust-building should entail efforts to acknowledge, understand, and reduce the present-day incidence of harmful patient experiences with practitioners.…”
Section: Jama Network Open | Oncologymentioning
confidence: 80%
“…27 This perceived-and possibly internalized stigma-may have consequences such as patients with tobacco-related cancers choosing to avoid or delay engaging in tobacco cessation services. [27][28][29] Depression or depressive symptoms are known barriers to cessation, and this appears generalizable to oncology patients. Indeed, a smoking cessation clinical trial found that patients with tobacco-related cancers reported significantly higher levels of depression than patients with non-tobacco-related cancers, 15 and this predicted smoking relapse.…”
Section: Discussionmentioning
confidence: 99%